2011
DOI: 10.1177/1934578x1100601220
|View full text |Cite
|
Sign up to set email alerts
|

HPLC/PDA/ESI-MS Evaluation of Saffron (Crocus sativus L.) Adulteration

Abstract: The present study evaluated the reliability of the ISO/TS 3632-2 UV-Vis spectrometric method for saffron classification, making experiments on saffron samples to which were added increasing concentrations of common saffron spice adulterants (safflower, marigold and turmeric). The results showed that the ISO/TS 3632-2 method is not able to detect addition of up to 10-20%, w/w, of saffron adulterants. For additions from 20 to 50%, w/w, of the three adulterants, saffron was classified in a wrong category; additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…Also, the UV-Vis spectrophotometric method proposed by ISO 3632-2 (ISO, 2010) may not detect saffron contamination with amounts of up to 20% (w/w) of safflower or turmeric, as it was recently reported (Sabatino, Scordino, Gargano, Belligno, Traulo, & Gagliano, 2011). For the detection of plant adulterants in saffron, several chromatographic (Alonso, Salinas, & Garijo, 1998;Haghighi, Feizy, & Hemati Kakhki, 2007;Lozano, Castellar, Simancas, & Iborra, 1999;Sabatino et al, 2011;Sampathu, Shivashankar, Lewis, & Wood, 1984) and molecular (Babaei, Talebi, & Bahar, 2014;Javanmardi, Bagheri, Moshtaghi, Sharifi, & Hemati Kakhki, 2011;Ma, Zhu, Li, Dong, & Tsim, 2001;Marieschi, Torelli, & Bruni, 2012;Torelli et al, 2014) methods have been employed so far with encouraging results. The use of DNA markers has allowed the detection of low amounts (up to 1%) of several bulking materials including safflower and turmeric (Javanmardi et al, 2011;Marieschi et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Also, the UV-Vis spectrophotometric method proposed by ISO 3632-2 (ISO, 2010) may not detect saffron contamination with amounts of up to 20% (w/w) of safflower or turmeric, as it was recently reported (Sabatino, Scordino, Gargano, Belligno, Traulo, & Gagliano, 2011). For the detection of plant adulterants in saffron, several chromatographic (Alonso, Salinas, & Garijo, 1998;Haghighi, Feizy, & Hemati Kakhki, 2007;Lozano, Castellar, Simancas, & Iborra, 1999;Sabatino et al, 2011;Sampathu, Shivashankar, Lewis, & Wood, 1984) and molecular (Babaei, Talebi, & Bahar, 2014;Javanmardi, Bagheri, Moshtaghi, Sharifi, & Hemati Kakhki, 2011;Ma, Zhu, Li, Dong, & Tsim, 2001;Marieschi, Torelli, & Bruni, 2012;Torelli et al, 2014) methods have been employed so far with encouraging results. The use of DNA markers has allowed the detection of low amounts (up to 1%) of several bulking materials including safflower and turmeric (Javanmardi et al, 2011;Marieschi et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…At present, there is a growing tendency to nd quick, simple, and powerful tools which enable detection of saffron metabolites for quality and fraud control. [9][10][11][12] Considering that the sensory characteristics (avor, taste, color) and particular properties (health benets) of saffron are essentially determined by its chemical content, the application of MS-based chemical component proling offers signicant opportunities to obtain precious detailed information that can be directly correlated to the spice quality. Mass spectrometry is a wellestablished method for the high-throughput detection and quantitative analysis 13 of metabolites, 14 amino acids and their synthetic analogues, 15 and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ISO 3632 standards are non-specific and unable to separate authentic and adulterated saffron adequately. In particular, it has been demonstrated that a contamination of ground saffron with amounts of up to 20 % (w/w) of Calendula flowers, safflower, or turmeric was not revealed by the ISO 3632 standards, as it was recently reported [9].…”
Section: Introductionmentioning
confidence: 90%
“…Various authors have proposed several analytical methods for the detection of plant adulterants in saffron, such as UVvis spectrophotometric measurements [10][11][12], near infrared spectroscopy [13], Raman and nuclear magnetic resonance spectroscopy (NMR) [14,15], capillary electrophoresis [16], and high-performance liquid chromatography without and with mass spectrometry (MS) detection [9,[17][18][19]. Most of these methods used to detect adulteration of saffron are based on the analysis of target compounds and therefore have a major drawback related with the fact that they can only detect a limited number of adulterations.…”
Section: Introductionmentioning
confidence: 99%